Proceedings of the 2016 6th International Conference on Machinery, Materials, Environment, Biotechnology and Computer 2016
DOI: 10.2991/mmebc-16.2016.164
|View full text |Cite
|
Sign up to set email alerts
|

Specific Emitter Identification based on the Energy Envelope of Transient Signal

Abstract: Abstract. Specific Emitter Identification (SEI) is the method to identify the individual radio emitter using the transmitted signals' characteristic called Radio Frequency Fingerprint (RFF), which are originated from transmitter imperfections. A novel SEI approach to extract transient fingerprint features of energy envelope of transient signals is proposed in this paper. The origin of energy envelop is explored, and a nonlinear system model is utilized to explain how the features of energy envelope produce. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…A study suggested a Specific Emitter Identification as a method to achieve transient fingerprint characteristics of obtained energy envelope of transient signals [1]. This research introduces a new algorithm that employs the phase features for detection determinations [2].…”
Section: Introductionmentioning
confidence: 99%
“…A study suggested a Specific Emitter Identification as a method to achieve transient fingerprint characteristics of obtained energy envelope of transient signals [1]. This research introduces a new algorithm that employs the phase features for detection determinations [2].…”
Section: Introductionmentioning
confidence: 99%